2012
DOI: 10.1111/j.1744-7976.2012.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and the Environmental Kuznets Curve in Developing Countries: A Panel Smooth Transition Regression Approach

Abstract: Deforestation is a serious environmental problem in many developing countries. This study re-examines whether the Environmental Kuznets Curve (EKC) relationship between deforestation and real income exists for 52 developing countries during the 1972-2003 period by applying the recently developed panel smooth transition regression (PSTR) model. This paper also considers the potential endogeneity biases and other explanatory variables as a robustness check of the EKC hypothesis. The empirical results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 49 publications
2
28
0
3
Order By: Relevance
“…Until now, the wide empirical macroeconomic studies on deforestation (using panel data on deforestation at a country level, provided by FAO) have given useful results concerning the factors that account for periodic deforestation rates (annual or over a five-year period). First, the literature questioned the impact of economic development on deforestation, by investigating the existence of an Environmental Kuznets Curve for deforestation (most recently Culas (2012); Busa (2013); Chiu (2012)). Those studies bring very contrasted results, as shown in the meta-analysis by Choumert et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the wide empirical macroeconomic studies on deforestation (using panel data on deforestation at a country level, provided by FAO) have given useful results concerning the factors that account for periodic deforestation rates (annual or over a five-year period). First, the literature questioned the impact of economic development on deforestation, by investigating the existence of an Environmental Kuznets Curve for deforestation (most recently Culas (2012); Busa (2013); Chiu (2012)). Those studies bring very contrasted results, as shown in the meta-analysis by Choumert et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The PSTR model was first applied by González et al (2005) to examine the effect of capital market imperfections on investment. This methodology has been commonly used in finance [61] and recently, in energy and environmental economics [62][63][64][65]. However, the public infrastructure-energy intensity relationship has not been studied from this perspective.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, PSTR can be thought of as a regime-switching model that allows for a small number of extreme regimes to be associated with the extreme value of a transition function and where the transition from one regime to another is smooth. Second, we follow Chiu (2012), who applied the PSTR model to examine the Environmental Kuznets Curve (EKC) for 52 developing countries from 1972 to 2003. Duarte et al (2013) also employed the PSTR model to analyse the relationship between water use per capita and income per capita of 65 countries over the period of 1962 to 2008.…”
Section: Methodology Model Specifications and Variable Constructionsmentioning
confidence: 99%